2008
DOI: 10.1177/001440290807400203
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum-Based Measurement in Writing: Predicting the Success of High-School Students on State Standards Tests

Abstract: We examined the technical adequacy of writing progress measures as indicators of success on state standards tests. Tenth-grade students wrote for 10 min, marking their samples at 3, 5, and 7 min. Samples were scored for words written, words spelled correctly, and correct and correct minus incorrect word sequences. The number of correct minus incorrect word sequences written in 7 and 10 min yielded the highest reliability and validity coefficients. Tables of Probable Success were created to illustrate the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 26 publications
3
51
2
1
Order By: Relevance
“…Another study illustrated that %CWS yielded the strongest correlation when compared with seven other metrics (Amato & Watkins, 2011). Collectively, this evidence suggests that CWS, %CWS, or CIWS appears to hold the most promise for screening (Espin et al, 2000, 2005, 2008; McMaster & Campbell, 2008). That being said, WW is an index commonly used in school practice (McMaster & Espin, 2007) likely because it is highly reliable and requires less time to score than CWS (Gansle, Noell, VanDerHeyden, Naquin, & Slider, 2002).…”
Section: Technical Features Of Cbm Static Scores At the Secondary Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study illustrated that %CWS yielded the strongest correlation when compared with seven other metrics (Amato & Watkins, 2011). Collectively, this evidence suggests that CWS, %CWS, or CIWS appears to hold the most promise for screening (Espin et al, 2000, 2005, 2008; McMaster & Campbell, 2008). That being said, WW is an index commonly used in school practice (McMaster & Espin, 2007) likely because it is highly reliable and requires less time to score than CWS (Gansle, Noell, VanDerHeyden, Naquin, & Slider, 2002).…”
Section: Technical Features Of Cbm Static Scores At the Secondary Levelmentioning
confidence: 99%
“…Although CBM metrics correlate independently with important achievement outcomes, many researchers and educators express concern that CBM may not be targeting the most important components of desired achievement (Amato & Watkins, 2011; Espin et al, 2008; Foegen et al, 2007; Mercer et al, 2012; Wayman et al, 2007). Therefore, it may take more than one construct to explain variance in expected outcomes.…”
Section: Relationship Among Cbm Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…To explain, over the years my colleagues and I have worked on the development of a writing progress monitoring system (often referred to as Curriculum-Based Measurement; Deno, 1985) to track the writing progress of students with learning disabilities (LD) within a school year (see, e.g., Espin, De La Paz, Scierka, & Roelofs, 2005;Espin, Wallace, Campbell, Lembke, Long, & Tichá, 2008;McMaster, & Espin, 2007). Although our system has a slightly different goal than that of Burdick et al (2013), we too needed to develop a definition or conceptualization of "good writing" to guide our work, specifically in the selection of our criterion variables.…”
Section: A Espinmentioning
confidence: 99%
“…Research-validated measures with demonstrated reliability and validity for assessing both level and growth in student performance exist in the areas of early literacy and numeracy, reading, reading comprehension, mathematics, handwriting, spelling, and written expression (L. S. ; National Center on Response to Intervention, 2010). These measures have more commonly been evaluated for elementary and middle school populations, but recent research has shown them to be valid for measuring performance of secondary students as well (e.g., Espin et al, 2008).…”
Section: Schoolwide Screening and Progress Monitoringmentioning
confidence: 99%